Semaglutide Alleviates LPS-Induced Cognitive Disorder via O-GlcNAcylation of AKT-mTOR Signaling Pathway Components - Qiangwei Liu; Lu Chen; Mengxue Zhang; Zhun Wang; Xiaokun Wang; Ying Dong; Kaiyuan Wang; Changyu Jiang; Yiqing Yin (NeuroMolecular Medicine, 2026)

Stability Charts for Blast Disturbed Zone of Rock Slope Using Hoek–Brown Failure Criterion - Yu Lu; Changyu Jin (Rock Mechanics and Rock Engineering, 2026)

Quantifying near-surface soil evaporation losses in semi-arid shrublands using lc-excess–coupled Rayleigh fractionation: Evidence from the Hunshandake Sandy Land, China - Yusheng Hao; Debin Jia; Weiying Feng; Yibo Zhao; Mingyu Ji; Lina Yang (Plant and Soil, 2026)

Unlocking green development through clean energy innovation networks: structural evolution and factor flow mechanisms - Yan Bu; Bole Zhang; Ziyu Jiang; Mingye Ai (Environment, Development and Sustainability, 2026)

Nonlinear responses of phytoplankton size, diversity, and chlorophyll a to environmental forcing along the Yellow Sea - Minghao Li; Yuqiu Wei; Haoyu Jin; Dong Xu; Chao Wu; Shujin Guo; Zhengguo Cui; Dongsheng Ding (Marine Pollution Bulletin, 2026)

A frequency-informed adaptive variable-step model predictive control framework with stability guarantees for cascade canals - Minghan Yang; Chao Wang; Lina Zhang; Pengyu Jin; Ke Xu; Hao Wang (Advances in Water Resources, 2026)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Species interactions mediate arbuscular mycorrhizal fungi successional dynamics and glomalin-related soil protein accumulation in volcanic ecosystems - Pengfei Wang; Xinyan Liu; Yaxin Zheng; Hanting Qu; Jingpeng Li; Ruiping Wang; Yu Ji; Da Xu; Fucheng Ding; Peng Zhang; Haijing Liu; Yuying Bao (Applied Soil Ecology, 2025)

Effects of simulated root exudate C:N stoichiometry on key microbial taxa and microbial respiration - Jiajia Li; Zhenhao Wei; Wei Guo; Kang Zhang; Xiaoyu Jia; Zhouping Shangguan (Applied Soil Ecology, 2025)

The coupling effects of long-term straw return and plant selection facilitate rhizosphere nitrogen supply by promoting recruitment of core genera - Lei Xu; Yan Zhou; Congrong Miao; Jianwei Zhang; Yanfeng Ding; Zhenghui Liu; Weiwei Li; Yu Jiang; Ganghua Li (Applied Soil Ecology, 2025)

Processes of assembly of endophytic prokaryotic and rhizosphere fungal communities in table grape are preponderantly deterministic - Muxi Xie; Jiyu Jia; Dongdong Luan; Ruipeng Li; Jiangzhou Zhang; Junling Zhang (Applied Soil Ecology, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Immune response of pearl oysters to stress and diseases - Linda Adzigbli; Ruijuan Hao; Yu Jiao; Yuewen Deng; Xiaodong Du; Qingheng Wang; Ronglian Huang (Reviews in Aquaculture, 2020)
Pearl oysters are found in the marine ecosystem. Due to their frequent exposure to microbial pathogens and environmental perturbations, they have developed a multifaceted innate immune system with differentially expressed immune‐related genes in response to a range of stress via vast coordinated immune reactions, such as immune recognition, signal transduction, synthesis of antimicrobial peptides, encapsulation and phagocytosis of the circulating haemocytes. The species are farmed to produce pearls. With the increasing adoption of aquaculture techniques in pearl production, there is the need to understand their culture environment and their immune response mechanisms. Multi‐omic studies have documented responses to nuclei insertion operation, diseases and various environmental conditions in Pinctada fucata martensii (Dunker, 1880), Pinctada maxima (Jameson, 1901), Pinctada margaritifera and Pteria penguin (Roding, 1798). Among the various stressors, nuclei insertion operation has been identified as a prevailing factor modifying gene expression. Other factors include life stage, air exposure, temperature, salinity, metals and organic contaminants. This manuscript details the response mechanism of these pearl oysters to the various stressors.